Increased Expression of SETD7 Promotes Cell Proliferation by Regulating Cell Cycle and Indicates Poor Prognosis in Hepatocellular Carcinoma. - Yuanyuan Chen; Shengsheng Yang; Jiewei Hu; Chaoqin Yu; Miaoxia He; Zailong Cai (PLoS ONE)
Purpose To investigate the role of SET domain containing 7 (SETD7) in hepatocellular carcinoma (HCC) and determine whether SETD7 can be used as a predictor of overall survival in HCC patients. Methods mRNAs and proteins of SETD7 and related genes in HCC tumor samples and paired adjacent non-tumorous liver tissues (ANLTs) (n = 20) or culture cells were determined by quantitative real-time PCR and Western blot. Cell proliferation and apoptosis with SETD7 knockdown SMMC-7721 cells or SETD7 overexpressed HepG2 cells were analyzed by CCK8 assay or flow cytometry. Gene expression alterations in SETD7 knockdown of SMMC-7721 cells were determined by digital gene expression (DGE) profiling. Defined data on patients (n = 225) with HCC were retrieved for the further study. Tissue microarrays (TMAs) were performed using paraffin tissues with tumor and ANLTs. SETD7 and related proteins were determined by TMAs immunohistochemistry. Statistical analyses were conducted to associate SETD7 expression with tumor features and patient outcomes, as well as related proteins expression. Results SETD7 expression was significantly higher in HCC tumor tissues than in ANLTs. SETD7 overexpression in vitro can promote HepG2 cell proliferation, whereas SETD7 knockdown can inhibit SMMC-7721 cell proliferation by regulating the cell cycle. SETD7 expression was significantly correlated with five genes expression. Increased SETD7 is associated with metastasis, recurrence, large tumor size, and poor tumor differentiation, and indicates poor prognosis in HCC patients. Conclusions SETD7 plays a critical role in HCC, and its immunohistochemistry signature provides potential clinical significance for personalized prediction of HCC prognosis.